Nano DNA Vaccine Encoding Toxoplasma gondii Histone Deacetylase SIR2 Enhanced Protective Immunity in Mice - Zhengqing Yu; Yujia Lu; Wandi Cao; Muhammad Tahir Aleem; Junlong Liu; Jianxun Luo; Ruofeng Yan; Lixin Xu; Xiaokai Song; Xiangrui Li (MDPI AG, 2021)
The pathogen of toxoplasmosis, Toxoplasma gondii (T. gondii), is a zoonotic protozoon that can affect the health of warm-blooded animals including humans. Up to now, an effective vaccine with completely protection is still inaccessible. In this study, the DNA vaccine encoding T. gondii histone deacetylase SIR2 (pVAX1-SIR2) was constructed. To enhance the efficacy, chitosan and poly (d, l-lactic-co-glycolic)-acid (PLGA) were employed to design nanospheres loaded with the DNA vaccine, denoted as pVAX1-SIR2/CS and pVAX1-SIR2/PLGA nanospheres. The pVAX1-SIR2 plasmids were transfected into HEK 293-T cells, and the expression was evaluated by a laser scanning confocal microscopy. Then, the immune protections of pVAX1-SIR2 plasmid, pVAX1-SIR2/CS nanospheres, and pVAX1-SIR2/PLGA nanospheres were evaluated in a laboratory animal model. The in vivo findings indicated that pVAX1-SIR2/CS and pVAX1-SIR2/PLGA nanospheres could generate a mixed Th1/Th2 immune response, as indicated by the regulated production of antibodies and cytokines, the enhanced maturation and major histocompatibility complex (MHC) expression of dendritic cells (DCs), the induced splenocyte proliferation, and the increased percentages of CD4+ and CD8+ T lymphocytes. Furthermore, this enhanced immunity could obviously reduce the parasite burden in immunized animals through a lethal dose of T. gondii RH strain challenge. All these results propose that pVAX1-SIR2 plasmids entrapped in chitosan or PLGA nanospheres could be the promising vaccines against acute T. gondii infections and deserve further investigations.